The role and value of fieldwork in library and information science education a case study of the LIS 181 (Field assignment) - Gelvezon, Lili Ann B. (2001)
Training programs such as fieldwork have reached an important place in the curriculum of almost any field of study, including Library and Information Science education. It is strongly held that making connections through fieldwork is the way to achieve the needed integration between theory and practice.